TOTAL QUALITY MANAGEMENT AS A STRATEGY FOR ENHANCING COMPETITIVE ADVANTAGE IN THE COURIER SERVICES SECTOR IN HARARE METROPOLITAN PROVINCE. - Thomas, Bhebhe; Mwendera, Rumbidzai; Obert, Sifile (IJRDO - Journal of Applied Management Science, 2019)
This study sought to assess the effectiveness of Total Quality Management and its impact on performance within the Zimbabwean courier services sector. The mixed research approach was used to gather both qualitative and quantitative data. Out of a sample of 220 respondents drawn from four courier service companies, the findings revealed that courier firms in Harare consider TQM as a cost which is difficult to implement given their financial constraints, but they are aware of its importance in achieving competitive advantage. The study also found out that insufficient resources, lack of management commitment, lack of appropriate training and poor planning are the barriers to implementing TQM in the courier services sector. The study concluded that there is a positive relationship between implementation of TQM and company performance. It was recommended that in order to improve performance and increase viability and impact, courier services companies should fully adopt TQM including its SERVQUAL Model as a way of attaining competitive advantage. It was further recommended that courier services companies should address the barriers that hinder the adoption of TQM in order to succeed in producing superior goods and services.